ECONOMIC GROWTH, TRADE AND ENVIRONMENTAL ISSUES: TESTING ENVIRONMENTAL KUZNETS CURVE - Dedi Budiman Hakim (Economic Journal of Emerging Markets, 2011)
ASEAN experiences a dynamic economic growth due to its liberalised markets. However concerns arise related to environmental issues resulting from the economic activities. It reflects tradeoffs between economic growth driven by trade and foreign direct investment (FDI), and environment. To investigate such a relation the Environmental Kuznets Curve was applied by regressing amount of carbon emission with gross domestic product (GDP), quadratic GDP, trade openness and FDI. The result reveals that amount of carbon emission is linearly and positively correlated with GDP per capita. It is predicted that as ASEAN economies grow, carbon emission increases. Trade openness is also found to contribute to carbon emission. Keywords: Kuznets curve, carbon emission, gross domestic product, trade, foreign direct investment JEL classification number: F15, F18